Demonstration of a multi‐species, multi‐response state‐and‐transition model approach for wildlife management. Issue 12 (14th December 2021) - Long, Ashley M.; Colón, Melanie R.; Morrison, Michael L.; Mathewson, Heather A.
Abstract: Land management agencies have collaborated to standardize assessments of rangeland health. These assessments incorporate state‐and‐transition concepts of ecosystem function using ecological site descriptions (ESDs) initially developed to provide information on the soil, topography, climate, and vegetation at areas of interest. Combined, ESDs and state‐and‐transition models (STMs) describe existing and potential plant community dynamics. Unlike previous methods used to assess rangeland health, STMs take into account that multiple states exist in space and time across sites and that reversible and directional changes in vegetation can occur in response to factors such as fire, erosion, weather, and management activities. Wildlife responses are seldom incorporated into this framework. However, combining STMs, ESDs, and species‐specific habitat use and demographic data could provide land managers with tools that classify current ecosystem conditions, predict vegetative change, and inform management for maintaining or improving key habitat features for species of interest. To demonstrate a multi‐species, multi‐response STM approach for wildlife management, we quantified vegetation structure and composition as a function of time since prescribed burning and wildfire in four geographically distinct study areas. We found no significant differences in the topographic or vegetative characteristics of ecological sites within our study areas. Thus, we visualized habitat use and demographic data for our two avian study species, the golden‐cheeked warbler ( Setophaga chrysoparia ) and the black‐capped vireo ( Vireo atricapilla ), along with plant community transformations, in a single STM per study area. Our research demonstrates how STMs could be operationalized for wildlife management in such a way that accounts for co‐occurring species with contrasting habitat requirements. In addition, our approach further illustrates how STMs could provide land managers with guidance to minimize the negative effects or enhance the positive effects of disturbance and management activities on wildlife.